2016
DOI: 10.18821/0023-2149-2016-94-10-764-769
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and personality features of patients with irritable bowel syndrome and bowel inflammatory diseases

Abstract: Objective. To conduct a comparative analysis of the emotional and personality characteristics ofpatients with irritable bowel syndrome (IBS) and inflammatory bowel disease (IBD) in remission with IBS-like symptoms. Patients and methods. This study carried out based at a specialized gastroenterology clinic in the period from 2010 to 2015 included 125 patients with IBS (IBS-D - 46, IBS-C - 20, IBS-M - 59) and 37 patients with IBD in remission: Crohn's disease (CD) - 11 and ulcerative colitis (UC) -26 patients. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The excluded publications did not fulfill the inclusion criteria as two were systematic reviews, three were conference/meeting abstracts, and one was out of scope. Thus, the remaining 10 publications were full text reviewed, and five of them were removed for the following reasons: two did not provide English full text as they were written in Portuguese (Amorim and Guerra, 2018 ) and Russian (Mnatsakanyan et al, 2016 ), one did not provide empirical data about alexithymia (Edman et al, 2017 ), and two were not specifically addressed to patients with IBD (Cozzolongo et al, 2015 ; Schauer et al, 2019 ). We concluded that five papers could be included in our systemic review based on the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…The excluded publications did not fulfill the inclusion criteria as two were systematic reviews, three were conference/meeting abstracts, and one was out of scope. Thus, the remaining 10 publications were full text reviewed, and five of them were removed for the following reasons: two did not provide English full text as they were written in Portuguese (Amorim and Guerra, 2018 ) and Russian (Mnatsakanyan et al, 2016 ), one did not provide empirical data about alexithymia (Edman et al, 2017 ), and two were not specifically addressed to patients with IBD (Cozzolongo et al, 2015 ; Schauer et al, 2019 ). We concluded that five papers could be included in our systemic review based on the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Patients often have a high level of neuroticism, anxiety, depressive states, and "somatovegetative disorders." Anxiety is observed in approximately 50% of patients with functional GIT diseases [82][83][84][85][86][87][88][89][90][91]. It is known that anxiety is induced by a stress response mediated primarily through the release of corticotropin-releasing hormone from the hypothalamus.…”
Section: Evolution Of Ideas About Functional Diseases Of the Gastroin...mentioning
confidence: 99%
“…ψυχή means soul and σ μα means body. Psychosomatic medicine is a branch of medical psychology that studies the influence of psychological factors on the occurrence, course, and outcome of somatic (body) diseases [86][87][88][89][90][91]. The Rome Process and the Rome Criteria are an international effort to collect scientific data that can help in the diagnosis and treatment of functional psychosomatic gastrointestinal disorders [82][83][84].…”
Section: Problems and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation